1981
DOI: 10.1093/ptj/61.8.1158
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Effects of Upper Extremity Proprioceptive Neuromuscular Facilitation Patterns

Abstract: Electromyography was used to determine the presence of electrical activity in the nonexercised latissimus dorsi, infraspinatus, and pectoralis major muscles while the contralateral limb underwent the proprioceptive neuromuscular facilitation pattern of flexion, abduction, external rotation with elbow straight and extension, adduction, internal rotation with elbow straight. Activity was present in all of these muscles during both components of the pattern. There was no significant difference in activity for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 4 publications
2
27
0
12
Order By: Relevance
“…As a reason for this, stretching was shown to be able to mobilize spinal reflexes and action mechanisms were formed at spinal cord (Nelson et al 2012). The effects of PNF on contralateral parts which are not exercised were shown at previous studies (Markos 1979, Pink 1981. In terms of the positive effects of regular stretching exercises in long-term, it was stated that flexibility can be preserved or increased as a result of stretch tolerance, and also it can positively affect elastical energy recovery capacity without affecting the explosive strength (Pacheco et al 2011).…”
Section: Positive Effects Of Pnf Stretching On Athletic Performancementioning
confidence: 86%
“…As a reason for this, stretching was shown to be able to mobilize spinal reflexes and action mechanisms were formed at spinal cord (Nelson et al 2012). The effects of PNF on contralateral parts which are not exercised were shown at previous studies (Markos 1979, Pink 1981. In terms of the positive effects of regular stretching exercises in long-term, it was stated that flexibility can be preserved or increased as a result of stretch tolerance, and also it can positively affect elastical energy recovery capacity without affecting the explosive strength (Pacheco et al 2011).…”
Section: Positive Effects Of Pnf Stretching On Athletic Performancementioning
confidence: 86%
“…Among the PNF's principles, irradiation is a useful aspect for patients with muscle weakness in areas that cannot be directly worked (strengthened) [5]. This principle is based on fact that stimulation of strong and preserved muscle groups produces strong activation of injured and weak muscles, facilitating muscle contraction [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, all patients showed a higher RMS activation in the TA muscle in the final assessment at the end of the PNF protocol. To obtain this result, we used an indirect treatment based on the concept of muscle force irradiation which occurs ipsilateral and contralateral to the performed diagonal 19,26 . In 1979, Markos 27 showed the feasibility of this treatment modality by increasing the EMG activity and the degree of hip flexion in normal individuals.…”
Section: Discussionmentioning
confidence: 99%